(untitled) (Research, Society and Development, 2020)
It is called the tooth that, when the chronological time of eruption arrives, remains partially or totally enclosed within the alveolar bone, with preservation or not of the pericoronal follicle. When not associated with any disorder, they can be used. Among the methods of utilization of impacted teeth, we can mention the accompaniment, orthodontically assisted eruption or transplant. The objective of this study was to report two cases of use of included teeth. Case 1 - Female patient, 15 years old, leucoderma, normossystemic, was referred by her orthodontist for orthopedic traction of elements 13 (upper right canine) and 23 (upper left canine) included. Clinical intraoral examination revealed absence of the same. The treatment consisted in the surgical exposition of elements 13 and 23 by the technique of apical repositioning of the flap (open technique) and orthodontic button gluing for posterior traction. Case 2 - Female patient, 20 years old, feoderma, normosystemic, presented for exodontia of element 37 (second molar inferior left). The intra-oral clinical examination revealed great coronary destruction in said element by dental caries. Due to the impossibility of other treatments, it was planned to remove the same and subsequent autogenous transplantation of element 38. We chose to perform the transplantation in a single (immediate) session. It is important for the dental surgeon to know and know the techniques of tooth utilization, as well as their advantages and disadvantages, in order to optimize their use and minimize the inconveniences arising from dental inclusion.